1979
DOI: 10.1002/pssb.2220910135
|View full text |Cite
|
Sign up to set email alerts
|

Hopping conductivity in heavily doped strongly compensated GaAs

Abstract: The hopping conductivity in heavily doped and closely compensated LPE gallium arsenide is investigated in the temperature range 4.2 to 250 K. It is found that the resistivity in n-type samples

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The obtained linear In u -T-112 law over about 2.5 orders of magnitude in temperature variation and more than three orders of magnitude of variation in conductivity is interpreted in the frame of a Coulomb gap with vanishing density of states a t the Fermi level, as predicted by Efros and Shklovskii. The preexponential factor eo = uK1 shows also scaling behaviour according to eo = ez(1n/nc)1.2*0 4 and a value of Q$ = 2.2 R cm. At n + nc co = ecl reaches the value of Mott's minimal metallic conductivity of U*ID.I~ = (Cezlh) nE13, with 0.025 5 C j 0.05.…”
mentioning
confidence: 89%
“…The obtained linear In u -T-112 law over about 2.5 orders of magnitude in temperature variation and more than three orders of magnitude of variation in conductivity is interpreted in the frame of a Coulomb gap with vanishing density of states a t the Fermi level, as predicted by Efros and Shklovskii. The preexponential factor eo = uK1 shows also scaling behaviour according to eo = ez(1n/nc)1.2*0 4 and a value of Q$ = 2.2 R cm. At n + nc co = ecl reaches the value of Mott's minimal metallic conductivity of U*ID.I~ = (Cezlh) nE13, with 0.025 5 C j 0.05.…”
mentioning
confidence: 89%
“…This is due to problems for the preparation of strongly and completely compensated semiconductors with high level of doping when Na 3 ӷ 1, where N is the impurity concentration and a is the Bohr radius. Moreover, some experimental studies were performed on wide-bandgap HDSC semiconductors, for example, GaAs, [8][9][10] in which may exist correlation in distribution of impurities. It is well known 6 that the amplitude and spatial size of potential relief in HDSC semiconductors may have a strong dependence on correlation in the impurity distribution, which reduces the potential fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…7 There have been numerous works, both theoretical and experimental, to investigate the influence of electrostatic potential fluctuations, formed by correlated and uncorrelated distributions of impurities, on the electrical and optical properties of various single-crystalline semiconductors. [6][7][8][9][10][11][12][13][14][15][16] However, the problem is quite complex, and there still remain a number of major theoretical and experimental challenges. Besides, there are no sufficiently experimental works on heavily doped semiconductors with very high degree of compensation, in particular, fully compensated.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the Hubbard‐band model is now used for analyzing the data on n ‐GaAs samples. While the impurity conduction in strongly compensated n ‐GaAs has been studied extensively, much less studies have been performed on weakly compensated n ‐GaAs. On the other hand, it is suggested that, in weakly compensated case, since σ 3 is small, impurity conduction will be dominated by the ϵ 2 process.…”
Section: Introductionmentioning
confidence: 99%